Mechanisms of TREM2 mediated immunosuppression and regulation of cancer progression - Lei, Xia; Gou, Ya Ni; Hao, Jin Yong; Huang, Xiao Jun (Frontiers in Oncology, 2024)
Cancer immunotherapy has recently emerged as a key strategy for cancer treatment. TREM2, a key target for regulating the tumor immune microenvironment, is important in cancer treatment and progression. TREM2 is an immune signaling hub that regulates multiple pathological pathways. It not only suppresses anti-tumor immune responses by inhibiting T cell-mediated immune responses, but it also influences tumorigenesis by affecting NK cell-mediated anti-tumor immunity. Noticeably, TREM2 expression levels also vary significantly among different tumor cells, and it can regulate tumor progression by modulating various signaling pathways. Above all, by summarizing the role of TREM2 in cancer immunotherapy and the mechanism by which TREM2 regulates tumor progression, this paper clarifies TREM2's role in both tumor progression and cancer therapy, identifying a new therapeutic target for oncology diseases.